2013
DOI: 10.1080/09503153.2013.775238
|View full text |Cite
|
Sign up to set email alerts
|

Supervision Found Wanting: Experiences of Health and Social Workers in Non-Government Organisations Working with Refugees and Asylum Seekers

Abstract: This paper explores the role and function of supervision, a neglected topic in research on social work with refugees and asylum seekers. Using semistructured interviews with health and social workers, supervision arrangements in non-government organisations (NGOs) in Australia and the UK are examined in the context of entitlement reductions and restricted access to services and support for service users. The comparative research highlights the demanding and ethically challenging nature of the work, and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 48 publications
(48 reference statements)
6
39
1
Order By: Relevance
“…This was especially the case among respondents suffering from resultant psychological strain. Supervision is an important tool in examining one’s own approach to work and stress, and can help to protect the health of social workers [43]. The study results might lead to the assumption that a lack of such support offers could even have a negative impact on worker health.…”
Section: Discussionmentioning
confidence: 99%
“…This was especially the case among respondents suffering from resultant psychological strain. Supervision is an important tool in examining one’s own approach to work and stress, and can help to protect the health of social workers [43]. The study results might lead to the assumption that a lack of such support offers could even have a negative impact on worker health.…”
Section: Discussionmentioning
confidence: 99%
“…Reflexivity was acknowledged by the authors (Robinson, ). The first author was a culturally and linguistically diverse migrant with the experience of working with refugees and asylum seekers in a clinical and research setting.…”
Section: Methodsmentioning
confidence: 99%
“…Although these adaptations are considered important for the services offered to culturally diverse individuals, there are still practitioners who are not adequately prepared for this clientele. Practitioners typically receive limited training to work with asylum seekers (Robinson, ), and there is limited research on how to work effectively with this population (Masocha & Simpson, ). Irrespective of the fact that practitioners need to be able to work with cultural diversity, there are still significant variations in training programmes addressing cultural competence, and many of the textbooks and training materials available reflect specific cultural contexts and may not be appropriate for different settings (Kirmayer, ).…”
mentioning
confidence: 99%
“…Supervisory support has been found to be positively linked to job satisfaction, particularly in child welfare social work (Burns, 2010), retention (Chen & Scannapieco, 2010;Dickinson & Painter, 2009), stress levels (Engstrom, 2017), developing professional identity (Moorhead, Bell, & Bowles, 2016) and greater perceptions of wellbeing (Mänttäri-van der Kuip, 2014). While licensing or full registration of social workers frequently mandates minimum hours of supervision, research demonstrates that compliance with such expectations can be patchy, as research in both Australia and England reported that practitioners did not receive regular supervision (Baginsky et al, 2010;Egan, 2012;Robinson, 2013;Turner-Daly & Jack, 2014). An English study explored the content and purpose of supervision for beginning practitioners (Manthorpe, Moriarty, Hussein, Stevens, & Sharpe, 2013) seeking the views of NQSWs and their managers on various elements of their support and development in their jobs.…”
Section: Supervision For Newly Qualifi Ed Social Workersmentioning
confidence: 99%